Lead adsorption from aqueous solution onto siderite - Erdem, M; Özverdi, A (Elsevier Science Bv, 2005)
In this paper, the ability of siderite to remove Pb2+ from aqueous solution by adsorption has been investigated through batch experiments. The Pb2+ adsorption property of the siderite was evaluated as a function of pH, siderite dosage, initial Pb2+ concentration, and temperature. Maximum Pb2+ adsorption yield was obtained to be 99.6% for initial Pb2+ concentration of 50 mg/1 at 25 degrees C and pH 2.97 for 180 min in the presence of 10 g/l siderite. Adsorption data obtained at 25, 30 and 35 degrees C showed that the adsorption process fitted first-order adsorption rate expression and Langmuir and Freundlich adsorption models. Adsorption capacities of siderite at 25, 30 and 35 degrees C were found to be 10.32, 12.45 and 14.06 mg Pb2+/g siderite, respectively. Adsorption enthalpy and activation energy values were calculated to be 49.73 and 32.49 kJ/g mot from the isotherm and kinetic data, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: lead removal; adsorption; siderite; heavy metal; wastewater treatment